Constructing Phenetic and Phylogenetic Relationship Using Clad'97 - Rahardi, Brian; Arumningtyas, Estri Laras; Mahmudi, Wayan Firdaus (Journal of Tropical Life Science, 2012)
Relationship construction has a very important position in classification process for arranging taxonomy of organism. In the world of taxonomy, there are two the most familiar relationship diagram, cladogram and phenogram. In every construction activity, a researcher is always facing character state data from taxa that becomes components of the diagram. Calculation that is used for construction is often incorporate iterative or repetitive process that needs time and precision. The existence of calculating tools that produces both text and graphical output are hopefully decrease time and error during construction. Basic algorithm that is used in calculation is for phylogenetic construction by Kluge and Farris in 1969,for phenetic construction using cluster analysis with slight modification. Basic common algorithm used in the software is by calculating two dimensional arrays of taxa x characters matrix and creating distance or similarity matrix. In more detail the program creates one dimensional array of taxonomical object and each object has some other one dimensional array containing data commonly exist in a taxonomic unit. The relationship between one object and theother are regulated by an object that created by class representing taxonomic tree. Cladogram is constructed by calculating nearest distance between each taxon (OTU) and creating one HTU in every bifurcation. Phenogram is constructed agglomeratively by searching highest similarity between taxon then grouped into new taxon. Program calculates numerical data after we do character scoring. Final result for each user may be different; this may be due to decision by user during construction process. This paper hopefully attracts people from systematic computation to develop further into open source software and multi-platform feature.